Iterated deferred correction for linear two-point boundary value problems - Cash, JR; Silva, HHM (Soc Brasileira Matematica Aplicada & Computacional, 1996)
An analysis of iterated deferred correction based on various classes of implicit Runge-Kutta formulae is given. Out of different possibilities considered, it is shown that those based purely on Lobatto formulae have the best stability. The enhanced stability of Lobatto schemes is very important for the efficient integration of excessively stiff boundary value problems and this is demonstrated by means of some numerical results.
Keywords: deferred correction; Lobatto formulae; Two-point boundary value problems